Patients' Prognosis in a Pakistani Hepato-Biliary Unit Treating Acute Severe Necrotizing Pancreatitis - Shah Faisal, Muhammad Imranullah, Muhammad Qammar Noshad, Arjan Kumar, Talha Rehman, Ulas Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The outcomes of individuals who were admitted to a hepatobiliary unit suffering from acute severe necrotizing pancreatitis will be the focus of this research. Study Design: Observational/ Prospective study Place and Duration: Conducted at Department of Gastroenterology Hayatabad Medical Complex Peshawar, during from the period Jan, 2021 to June, 2021. Methods: There were 85 patients of both genders were presented in this study. Included patients were aged between 20-70 years. All the patients had severe necrotizing pancreatitis were included. Detailed demographics of enrolled cases included age,sex, body mass index, etiology and comorbidities were recorded after taking informed written consent. Outcomes were calculated in terms of complications, hospital stay, number of drains inserted and nutritional support among all cases. SPSS 22.0 was used to analyze all data. Results: Among 85 patients, majority of the cases were males 62 (72.9%) and the rest of the patients were females 23 (27.1%). Included patients had mean age 47.12±8.39 years and had mean BMI 26.2±6.25 kg/m2. Most common comorbidity was diabetes mellitus found in 18 (21.2%),followed by hypertension in 17 (20%) and ischemic heart disease in 9 (10.6%) cases. Gall stones were the most common etiology found in 35 (41.2%) followed by idiopathic in 16 (18.8%) and cigarette smoking in 13 (15.3%) patients. NG feed was the most common nutrition in 19 (22.4%) cases. 10 was the most common CTSI score in 43 (50.6%) cases. Mean hospital stay was 31.9±11.82 days and infected necrosis / peri-pancreatic collections was the most common complication.13 (15.3%) cases received EUS drainage and surgical necrosectomy was given to 8 (9.4%) cases. Frequency of deaths was 10 (11.8%). Conclusion: A specialized hepato-biliary unit with a multidisciplinary team approach improves survival with acute severe necrotizing pancreatitis. Percutaneous and EUS-guided draining of pancreatic collections helps prevent necrosectomy for infected pancreatic necrosis. Keywords: Disease outcome, Acute pancreatitis, Infected pancreatic necrosis, Necrosectomy Acute Necrotizing Pancreatitis